Development and characterisation of Dioscorea hispida Dennst fibre-reinforced Dioscorea hispida Dennst starch biocomposite films - Kamaruddin, Zatil Hazrati (2021)
Plastic waste is one of the world's most critical problems and threats to human health, which is the third-largest waste source globally, with total plastic waste volume increasing in step with the growth in the global population and consumption per capita. Malaysia monitors global trends in plastic trash output and single-use plastics consumption while has been the world's biggest importer of plastic waste in 2017. These characteristics present many essential issues for the waste management system in the country. Biocomposites have attracted considerable attention due to their environmentally friendly and sustainable nature. Starch is the most promising material because of its natural biodegradability, renewability, and wide availability. Starches offer an attractive low-cost core of biodegradable polymer due to their low material cost and ability to be processed with conventional plastic processing equipment. Development and applications of biodegradable starch-based materials have attracted increasing attention since the well-recognised issues of oil shortage and the growing interest in easing the environmental burden due to extensive use of petrochemically-derived polymers. The main problems for developing starches as packaging films are the deficiencies of fragility, processability, high sensitivity to moisture and poor mechanical and water barrier properties. In order to transform native Dioscorea hispida starch (DHS) into high performance starch-based film for packaging application, dioscorea hispida fibre (DHF) was extracted from Dioscorea hispida tubers and reinforced the matrix of DHS. The DHS and DHF were extracted after removing the toxin of dioscorine by using the soaking process in sodium chloride for 5 days. The liquid chromatography electrospray ionisation mass spectrometric (LC-ESI-MS) systems were used to identify the presence of alkaloid dioscorine compounds within Dioscorea hispida tubers. The DHS and DHF were characterised in terms of chemical composition, density, moisture content, particle size distribution, SEM, TGA, FTIR, and XRD. Consequently, DHS biopolymer films were successfully developed using the solution casting method and, the optimum value of plasticizer concentration was 30% for the biopolymer film. The effect of different plasticiser types (glycerol (G), sorbitol (S) or sorbitol-glycerol combination (SG)) with varying concentrations (30– 60 %) on the physical, mechanical, thermal and, morphological properties of DHS biopolymer films were evaluated. The tensile strength of plasticised DHS films decreased, with increasing plasticiser concentrations. However, the anti-plasticisation effect showed in the elongation at break of G- and SG-plasticised films at 60% plasticiser concentration. Furthermore, the effects of different DHF loadings (3 – 9 wt%) on the physical, mechanical, biodegradability, thermal and morphological properties of biocomposite films were evaluated. The optimum value of fibre loading was 6% for the biocomposites film. The DHS based films had exhibited significant improvement in tensile strength with greater fibre content from 3 to 6 wt% and decreased at 9 wt% of loading. The addition of DHF within DHS biocomposites reduced the solubility of the film from 50.77 % (control film) to 36.0 % and 33.23 %, respectively, which proved that the films have good water stability. Overall, the results obtained from the current research showed that the development of fully biodegradable polymer films is crucial in the effort to highlight the ongoing environmental problems and gradually substitute the widely used conventional packaging materials.